The horizontal transfer of antibiotic resistance genes is enhanced by ionic liquid with different structure of varying alkyl chain length - Wang, Qing; Lu, Qian; Mao, Daqing; Cui, Yuxiao; Luo, Yi (Frontiers in Microbiology, 2015)
Antibiotic resistance genes (ARGs) have become a global health concern. In our previous study, an ionic liquid (IL) 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIm][PF6]) had been proven to facilitate the dissemination of ARGs in the environment. However, enhanced alkyl group chain length or the substitution of alkyl groups with the cation ring corresponded with increased antimicrobial effects. In this study, we investigated how different structures of ILs with 4, 6, and 8 C atoms in the longer alkyl chain on the imidazolium cations facilitated the dissemination of ARGs. The promotion of plasmid RP4 transfer frequency decreased with [CnMIM][BF4] increasing the alkyl chain length from 4 carbon atoms to 8 carbon atoms on the imidazolium cations, which is observed with [BMIM][BF4] (n = 4, 5.9 fold) > HMIM][BF4] (n = 6, 2.2 fold) > [OMIM][BF4] (n = 8, 1.7 fold). This illustrates that [CnMIM][BF4] with increasing the alkyl chain length exert decreasing ability in facilitating plasmid RP4 horizontal transfer, which is possibly related to IL-structure dependent toxicity. The IL-structure dependent plasmid RP4 transfer frequency was attributable to bacterial cell membrane permeability weaken with increasing alkyl chain length of [CnMIM][PF4], which was evidenced by flow cytometry. In freshwater microcosm, [CnMIm][BF4] promoted the relative abundance of the sulI and intI genes for 4.6 folds, aphA and traF for 5.2 folds higher than the untreated groups, promoting the propagation of ARGs in the aquatic environment. This is the first report that ILs with different structure of varying alkyl chain length facilitate horizontal transfer of plasmid RP4 which is widely distributed in the environment, and thus add the adverse effects of the environmental risk of ILs.